Migrant workers in the special economic zone towards economic and environmental impact using econometric modelling / Azyyati Anuar ... [et al.] - Anuar, Azyyati; Marwan, Nur Fakhzan; Siriyanun, Sirinya; Smith, John S.F. (2019)
The Thai government has prioritized the development of border areas connecting with neighboring countries in the ASEAN region. Songkhla Province has been designated as one such area. This means that Sadao, Hat Yai, and other cities in Songkhla Province have the potential to be economically important places. Songkhla’s border crossings with Malaysia are particularly important as they are the only border crossings in Thailand with cross-border railroad access. Because of this, the Thai government has designated a Special Economic Zone (SEZ) as well as Malaysian government is also planning the development of Malaysia’s first Special Border Economic Zone (SBEZ), labelled the Kota Perdana SBEZ. Since Thailand and Malaysia have relatively similar economies and levels of development, the conditions in all three of these locations namely Sadao, Bukit Kayu Hitam and Padang Besar will likely be comparable. Therefore, the lessons from one may be applied to the others.